An on-demand solar hydrogen-evolution system for unassisted high-efficiency pure-water splitting. Issue 29 (8th July 2019) - Che, Wei; Su, Hui; Zhao, Xu; Li, Yuanli; Zhang, Hui; Zhou, Wanlin; Liu, Meihuan; Cheng, Weiren; Hu, Fengchun; Liu, Qinghua
Abstract : A surface hydroxylation structure of g-C3 N3.5 (O0.5 H0.5 ) photocatalyst was designed to concurrently increase the toxicity resistance and maximize the charge separation for H2 evolution. Abstract : Solar water splitting of pure water offers an attractive means for sustainable and carbon-free H2 production. However, current photocatalytic H2 production systems still suffer from two basic issues: the kinetic bottleneck for O2 release and the easy toxicity of the photocatalysts. Here, we developed a consolidated photocatalyst, namely g-C3 N3.5 (O0.5 H0.5 ), that can boost sustainable and superior H2 evolution without using any sacrificial reagent. By conceptual design analysis as the guideline for three synthetic steps, the surface hydroxylation structure of g-C3 N3.5 (O0.5 H0.5 ) concurrently increases the toxicity resistance and maximizes the charge separation for H2 evolution. The obtained surface-hydroxylated g-C3 N3.5 (O0.5 H0.5 ) photocatalyst exhibited unassisted high-efficiency pure-water-splitting activity, with a benchmark H2 -evolution rate up to 947.7 μmol h −1 g −1 under visible-light irradiation. Notably, the quantum efficiency of the g-C3 N3.5 (O0.5 H0.5 ) suspension reached ∼10.6 and ∼2.5% at 420 and 520 nm, respectively, 10–20 times that of pristine g-C3 N4 . For the first time, we observed a key phenomenon that H2 O molecules can rapidly capture the photoexcited holes to produce H2 O2, which can greatly promote the efficient charge separation for high H2 evolution.